Ku is associated with the telomere in mammals - Hsu, Hsin-Ling (The National Academy of Sciences, 1999)
Telomeres are specialized DNA/protein complexes that comprise the ends of eukaryotic chromosomes. The highly expressed Ku heterodimer, composed of 70 and 80 K(d) subunits (Ku70 and Ku80), is the high-affinity DNA binding component of the DNA-dependent protein kinase. Ku is critical for nonhomologous DNA double-stranded break repair and site-specific recombination of V(D)J gene segments. Ku also plays an important role in telomere maintenance in yeast. Herein, we report, using an in vivo crosslinking method, that human and hamster telomeric DNAs specifically coimmunoprecipitate with human Ku80 after crosslinking. Localization of Ku to the telomere does not depend on the DNA-dependent protein kinase catalytic component. These findings suggest a direct link between Ku and the telomere in mammalian cells.